THE LITERARY LEGACY AND AESTHETIC VIEWS OF XURSHID DO‘STMUHAMMAD: HIS APPROACH TO LITERATURE AND ART IN HIS WORKS - Ubaydullayeva Gulruh G‘Ayratovna (American Journals Publishing, 2026)
This article outlines the literary and aesthetic vision of Xurshid Do‘stmuhammad, focusing on the philosophical depth, symbolic imagery, and ethical sensitivity of his poetry. His poems synthesize national memory with modern introspection, presenting the individual as both a witness to history and a seeker of inner harmony. Through restrained language and layered metaphors, Do‘stmuhammad explores themes of spiritual identity, moral responsibility, and the fragile balance between tradition and contemporary life. The analysis shows how his poetic voice transforms everyday experience into reflective insight, creating a bridge between personal emotion and collective consciousness.
Keywords: Uzbek poetry, aesthetics, symbolism, spiritual identity, national memory, modern introspection.